Do proton pump inhibitors harm to semen? Hyderabad Sindh based study - Imran Ali Shaikh; Naila Masood; Tariq Zaffar Shaikh (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2019)
Background: Proton pump inhibitors (PPIs) are widely used over counter drugs in Pakistan. Unjustified use of PPI is increasing .One concern of their use is spermatogenesis and male fertility. Objective: To observe the detrimental effects of proton pump inhibitors on various parameters of semen of younger individuals of Hyderabad sindh Pakistan. Duration of study: 1st June to 25thDec 2017. Place of study: private Clinics of sadder Hyderabad sindh Pakistan. Methodology: 109 patients were selected as per inclusion criteria. All were young subjects, age was 24 ±7.6 years. Mean duration of PPI was 2.5±2.7 months. None of subject was diagnosed infertility or sub fertility. Five parameters were assessed before and after PPI use. Sampling technique was non probability convenience. Statical software was SPSS 16. Student paired t test was used to calculate p value before and after PPI use. P value was considered <0.05 significant. Results: There was no significant impact noted over five parameters of semen p value was only significant in semen volume <0.05. Conclusion: There is no negative impact of PPI over five parameters of semen and male fertility.